Pengaruh Pengetahuan Masyarakat Tentang Produk, Pelayanan dan Lokasi Bank Dalam Memilih Jasa Bank Syariah di Kota Yogyakarta - Anisa Yuri; Mufti Alam Adha; Riduwan Riduwan (Prodi Perbankan Syariah FAI UMT, 2023)
AbstractThis study aims to test whether the variables of product knowledge, service knowledge, and knowledge of banking locations affect choosing Islamic bank services. This research was conducted using a quantitative methodology. Using a questionnaire and the research population is the people of Yogyakarta City. In this study, the sample uses purposive sampling with the criteria that people use Islamic bank services. Furthermore, in this study the data analysis used multiple linear regression analysis with an analytical tool, namely SPSS Version 23. The results illustrated that simultaneously the variables affected choosing Islamic bank products, namely F arithmetic 27.680 > 3.09 (F table). Partially the service knowledge variable with t count of 1.546 < 1.984 (t table) and location knowledge with t count of 1.635 < 1.984 (t table) do not affect choosing Islamic bank products.Keywords: Knowledge, Product, Service, Location, Islamic Bank.